2013
DOI: 10.1246/cl.130212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photovoltaic Properties of Phenylethynyl-substituted Diazaporphyrin

Abstract: Carboxyphenylethynyl-substituted diazaporphyrin has been synthesized to assess the utility of diazaporphyrins in dye-sensitized solar cells for the first time. The diazaporphyrin-sensitized TiO2 cell exhibited photocurrent generation in the visible region of 400–700 nm together with a power conversion efficiency of 0.08%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Dye-sensitized solar cells (DSSCs) have attracted much attention due to their excellent photovoltaic performance, low production costs, and environmentally friendly features. The original form of DSSCs has been realized in the ruthenium­(II) bipyridyl complexes where a solar-to-electric power conversion (PCE) of about 12% has been reported. , Despite a high PCE and tunability of electronic properties, their extensive application has been limited because of the rarity, requirement for careful synthesis, and environmental issues associated with ruthenium metal. , From this perspective, organic dyes with no metal or inexpensive metal complexes have become the central focus of DSSCs due to low-cost production and facile modulation of their electronic structure to improve their light-harvesting efficiency . An elegant strategy to improve the light-harvesting ability of the sensitizers is to use an electron donor (D, push) and electron acceptor (A, pull) group, connected via a π-conjugated bridge. , Separating donor from acceptor in the so-called donor−π–acceptor or push–pull dyes allows the spatial separation of electrons and holes and thus decreases their recombination rate (i.e., increasing exciton lifetimes).…”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs) have attracted much attention due to their excellent photovoltaic performance, low production costs, and environmentally friendly features. The original form of DSSCs has been realized in the ruthenium­(II) bipyridyl complexes where a solar-to-electric power conversion (PCE) of about 12% has been reported. , Despite a high PCE and tunability of electronic properties, their extensive application has been limited because of the rarity, requirement for careful synthesis, and environmental issues associated with ruthenium metal. , From this perspective, organic dyes with no metal or inexpensive metal complexes have become the central focus of DSSCs due to low-cost production and facile modulation of their electronic structure to improve their light-harvesting efficiency . An elegant strategy to improve the light-harvesting ability of the sensitizers is to use an electron donor (D, push) and electron acceptor (A, pull) group, connected via a π-conjugated bridge. , Separating donor from acceptor in the so-called donor−π–acceptor or push–pull dyes allows the spatial separation of electrons and holes and thus decreases their recombination rate (i.e., increasing exciton lifetimes).…”
Section: Introductionmentioning
confidence: 99%
“… a λ max (log ε), absorption maxima (logarithms of extinction coefficients). For details, see refs , , , , , , , , , , , and . …”
Section: Azaporphyrins and Related Compoundsmentioning
confidence: 99%
“…The treatment of Br-MDAPs 72M (M = Zn, Ni) with tris(isopropyl)silylacetylene under standard Sonogashira reaction conditions, followed by the deprotection of the silyl group in the coupling products, afforded the corresponding 3-ethynyl-MDAPs 76M in 87−91% yields (Scheme 39). 148,149 Furthermore, ethynyl-ZnDAP 76Zn underwent a second Sonogashira reaction with ethyl p-iodobenzoate to give 3-(4carboxypheny)ethynyl-ZnDAP 77 in 24% yield after alkaline hydrolysis. 148 Shinokubo et al reported the direct and regioselective functionalization of NiDAP 66Ni with organometallic reagents.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…In 2013, we reported the first example of a DAP‐based DSSC, in which P4 was used as a sensitizer (Figure ) . Unfortunately, the PCE of this P4 ‐based DSSC was very low (0.08 %), not only because of the small driving force for electron injection from the excited state of P4 to the CB of TiO 2 , but also owing to the insufficient light‐harvesting ability in the long‐wavelength visible region.…”
Section: Introductionmentioning
confidence: 99%